Native listening : language experience and the recognition of spoken words - Cutler, Anne (The MIT Press, 2012)
An argument that the way we listen to speech is shaped by our experience with our native language. Understanding speech in our native tongue seems natural and effortless; listening to speech in a nonnative language is a different experience. In this book, Anne Cutler argues that listening to speech is a process of native listening because so much of it is exquisitely tailored to the requirements of the native language. Her cross-linguistic study (drawing on experimental work in languages that range from English and Dutch to Chinese and Japanese) documents what is universal and what is language specific in the way we listen to spoken language. Cutler describes the formidable range of mental tasks we carry out, all at once, with astonishing speed and accuracy, when we listen. These include evaluating probabilities arising from the structure of the native vocabulary, tracking information to locate the boundaries between words, paying attention to the way the words are pronounced, and assessing not only the sounds of speech but prosodic information that spans sequences of sounds. She describes infant speech perception, the consequences of language-specific specialization for listening to other languages, the flexibility and adaptability of listening (to our native languages), and how language-specificity and universality fit together in our language processing system. Drawing on her four decades of work as a psycholinguist, Cutler documents the recent growth in our knowledge about how spoken-word recognition works and the role of language structure in this process. Her book is a significant contribution to a vibrant and rapidly developing field.